Characterization of Cr (VI) – Containing solid phase particles in dry dust deposition in Daejeon, South Korea. (December 2018) - Lee, Pyeong-Koo; Chang, Hye Jung; Yu, Soonyoung; Chae, Keun Hwa; Bae, Jee-Hwan; Kang, Min-Ju; Chae, Gitak
Abstract: Solid phase speciation of chromium in dry dust deposition and road paint was determined using transmission electron microscopy (TEM) and X-ray absorption spectroscopy (XAS). Spherical black carbon aggregates in dry dust deposition contained discrete nano-sized lead chromate (PbCrO4 ) and zinc chromate (ZnCrO4 ), which likely originated from yellow traffic paint and zinc chromate primer (corrosion resistant pigment), respectively based on their main applications. Road marking paint samples from auto roads included lead chromate particles whose size, shape, composition and crystal structure were similar to those in dry dust deposition. A slight difference was found at the particle boundary. Namely, lead chromate in traffic paint was encapsulated by silica-bearing matrix, while discrete lead chromate in the black carbon of dry deposition was rarely enclosed within silica-bearing matrix. The Cr K edge X-ray absorption near edge structure (XANES) spectrum for dry deposition showed the characteristic pre-edge resonance peak similar to the spectra for the Cr(VI) standard and road paint, but the lower intensity. The amount of Cr(VI) accounted for approximately 45% of the total Cr in the dust sample. The solid phase speciation of Cr observed using TEM and their valence states determined using XANES were consistent with the chemical speciation determined using the sequential extraction. The contribution of this study is that XANES was applied to identify Cr valance states in urban dust deposition and zinc chromate was found as a Cr(VI) phase in dry dust deposition using TEM. These study results provide novel data on Cr speciation and Cr(VI)-containing mineral phases in dry dust deposition and their potential sources. Based on the wide use of lead and zinc chromate, atmospheric contamination with these solid phase speciation of Cr(VI) is expected in other cities in the world. Graphical abstract: Image Highlights: Spherical black carbon aggregates with Cr were observed in dust dry deposition. Discrete nano-sized lead chromate and zinc chromate were observed in the aggregates. Yellow traffic road marking paint is a source of lead chromate particles in dust. Cr(VI) accounted for about 45% of the total Cr in the dust sample based on XANES. Abstract : Nano-size lead and zinc chromate particles were observed within spherical black carbon aggregates in dry dust deposition, and lead chromate originated from traffic paint on roads.